ضوابط الفتاوى المباشرة وتطبيقاتها في الواقع الماليزي: دراسة تحليلية تقويمية - Mohamed Rashid Bin Abdul Razak
This research aims to examine the issue of spontaneous fatwa and its practice in Malaysia and assess the extent to which it satisfies the parameters of a fatwa. This study employed the descriptive, inductive, and deductive approaches to describe the reality of this subject, search for and examine the opinions of scholars on the subject, and produce a reasonable and appropriate conclusion. The research data were collected via library and fieldwork methods. That is, the researcher referred to established sources in Islamic jurisprudence and its principles to search for the parameters of fatwa of scholars, as well as visiting fatwa institutions in Malaysia to obtain examples of spontaneous fatwa. To complete this study, the researcher did not limit its discussion to the theoretical perspective, but also to the practical aspect by examining and analysing examples of spontaneous fatwa in Malaysia and the extent to which they satisfy the parameters of fatwa. The study limited its scope to four examples of spontaneous fatwa issued by several state muftis. The researcher found that the term “spontaneous fatwa” is not specified in any religious laws of Malaysia. The researcher found it necessary to subdivide the term “fatwa” that is documented in Malaysian religious laws so as to include spontaneous fatwa. The researcher also discovered that some examples of spontaneous fatwa have fulfilled the parameters, while others have not, and suggests that fatwa collectively must be strengthened to address complex current issues by seeking the views of experts in the field so that the fatwas issued will meet the set parameters.